Hypercalcemia at diagnosis of diffuse large B‐cell lymphoma is not uncommon and is associated with high‐risk features and a short diagnosis‐to‐treatment interval. Issue 3 (17th April 2020) - Gauchy, Anne‐Cécile; Kanagaratnam, Lukshe; Quinquenel, Anne; Gaillard, Baptiste; Rodier, Cyrielle; Godet, Sophie; Delmer, Alain; Durot, Eric
Abstract: Diffuse large B‐cell lymphoma (DLBCL) is an aggressive type of non‐Hodgkin lymphoma. The prevalence of hypercalcemia in this neoplasm and its prognostic significance is unclear. We retrospectively evaluated the prevalence of hypercalcemia at diagnosis of DLBCL and explored associations of hypercalcemia with clinical factors and outcome. Outcome was assessed using event‐free survival at 24 months (EFS24). A total of 305 patients (248 de novo DLBCL and 57 transformed indolent lymphomas) diagnosed between 2006 and 2018 in Reims were analyzed. The prevalence of calcemia >10.5 mg/dL at diagnosis of de novo DLBCL and transformed indolent lymphomas was 23% and 26%, respectively. Hypercalcemia in de novo DLBCL was strongly associated with high‐risk features, especially with International Prognostic Index (IPI) components, but also with B symptoms, β2‐microglobulin, hemoglobin, and albumin levels. The diagnosis‐to‐treatment interval was significantly shorter for hypercalcemic patients ( P = .001). These associations with adverse prognostic factors translated into lower rates of EFS24 (HR = 1.66; 95% CI, 1.08‐2.54) and shorter PFS ( P = .0059) and OS ( P = .0003) for patients with lymphoma‐related hypercalcemia but not independently of IPI parameters. These data suggest that hypercalcemia is rather a biomarker of the underlying biological aggressiveness of DLBCL.